Embodied Activities in Face-to-face and Mediated Settings Social Encounters in Time and Space - Reber, Elisabeth; Gerhardt, Cornelia; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This edited book revisits the concept of social 'activities' from an interactional perspective, examining how verbal, vocal, visual-spatial and material resources are deployed by participants for meaning-making in social encounters. The eleven original chapters within this volume analyse activities based on video recordings of naturalistic and naturally occurring social encounters from face-to-face and mediated settings in Chinese, Dutch, English, French, and German. Informed primarily by the methodological approaches of Conversation Analysis and Interactional Linguistics, the authors study embodiment in space and time in three distinct types of situations: objects in space, complex participation frameworks, and affiliation and alignment. Moreover, the book includes a theoretical and methodological discussion of how activities are constituted and visibly embodied in interaction. It will be of interest to students and scholars in sociology and linguistics in general, and face-to-face and mediated interaction in particular. Elisabeth Reber is a postdoctoral researcher and lecturer in English Linguistics at the University of Würzburg, Germany. She is co-convener of the DFG-funded scientific network "Multimodality and Embodied Interaction" (with Cornelia Gerhardt) and author of the monograph Affectivity in Interaction: Sound Objects in English (2012). Cornelia Gerhardt is lecturer in English Linguistics at Saarland University, Germany. Her research interests include the interactional appropriation of media and the embodiment of language at the interface with social phenomena such as football and food. Her previous books include Appropriating Live Televised Football through Talk (2014) and Culinary Linguistics (2013).
Preface; Cornelia Gerhardt and Elisabeth Reber -- Part I. Introduction - theoretical and methodological issues -- Chapter 1. Embodied Activities; Cornelia Gerhardt and Elisabeth Reber -- Chapter 2. Activities as discrete organizational domains; Harrie Mazeland -- Chapter 3. Practices for showing, looking and videorecording: the interactional establishment of a common focus of attention; Lorenza Mondada -- Part II. Objects in Space -- Chapter 4. Intra-operative decision making in a teaching hospital; Jeff Bezemer, Ged Murtagh and Alexandra Cope -- Chapter 5. 'Showing' as a means of engaging a reluctant participant into a joint activity; Cornelia Gerhardt -- Chapter 6. Joint attention in passing (...) - what dual mobile eye-tracking reveals about gaze in coordinating embodied activities on a market; Anja Stukenbrock and An Nhi Dao -- Part III. Complex Participation Frameworks -- Chapter 7. Multiparty coordination under time pressure: The social organisation of handball team time-out activities; Christian Meyer and Ulrich von Wedelstädt -- Chapter 8. Punch and Judy politics? Embodying challenging actions in parliament; Elisabeth Reber -- Chapter 9. Assessments in transition: Coordinating participation framework transitions in institutional settings; Darren Reed -- Part IV. Affiliation and Alignment -- Chapter 10. Embodying empathy: On the negotiation of resources, rights and responsibilities in comforting actions; Maxi Kupetz -- Chapter 11. Negotiating activity closings with reciprocal head nods in Mandarin conversation; Xiaoting Li -- Chapter 12. Position expansion in meeting talk; Harrie Mazeland -- Part V. Epilogue -- Chapter 13. Epilogue; Cornelia Gerhardt and Elisabeth Reber.
Keywords: Pragmatics; Semiotics; Linguistics -- Methodology; Communication; Anthropological linguistics; Pragmatics; Semiotics; Research Methods in Language and Linguistics; Media and Communication; Linguistic Anthropology